Are we eating plastic? Science mapping of microplastic pollution in the aquatic food chain - Fauzi, Muhammad Ashraf; Muhammad Ashraf, Fauzi; Md Faizal, Ahmad; Mohd Hanafiah, Ahmad; Wider, Walton; Lee, Chia Kuang (Society of Environmental Toxicology and Chemistry, 2024)
This study evaluates the knowledge structure of microplastic pollution and its effects on the aquatic food chain. The presence of microplastics has seriously harmed the ecosystem. Through bibliometric analysis, 216 journal publications were retrieved from the Web of Science (WoS) from 2008 to 2023 (April), with no restriction in the time frame. Applying bibliographic coupling and co-word analysis, the emerging, current, and future themes of microplastic pollution are presented. Three research streams are derived from bibliographic coupling, centralized on the source of microplastic pollution and its impact. At the same time, research streams from co-word analysis are associated with overcoming the issue of microplastics in the ecosystem. This study's implications suggest three main principles to mitigate microplastic issues: (1) educating the public on the impact of microplastic pollution, (2) implementing holistic regulations and policies, and (3) developing treatment strategies through conventional, innovative, and hybrid approaches. Microplastic pollution is a global concern, requiring a holistic and comprehensive approach to overcome it. This review is the first to present a scientific mapping of the microplastics literature, which is a fundamental basis for future research on microplastic pollution and its impact on the ecosystem.